PENGARUH PRAKTIK KERJA LAPANGAN DAN PENGALAMAN BERORGANISASI TERHADAP KESIAPAN KARIR SISWA LULUSAN 2022-2024 SMK INFORMATIKA SUKMA MANDIRI CILEGON - syarif hidayatulloh, syarif; Yaqub, Hasan; H, Hikmatullah (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to determine the effect of field work practice (PKL) and organizational experience on career readiness of students graduating from SMK Informatika Sukma Mandiri Cilegon 2022–2024. The background is the still high rate of open unemployment among SMK graduates despite having participated in PKL and organizational activities. Using an associative descriptive quantitative method, data were obtained through questionnaires to 67 respondents and analyzed by validity and reliability tests, classical assumption tests, and multiple linear regression. The results showed: PKL had a significant positive effect on career readiness (t-count 3.568 > t-table 1.668; sig. 0.001 < 0.05). Organizational experience had a significant positive effect on career readiness (t-count 2.317 > t-table 1.668; sig. 0.024 < 0.05). Simultaneously, both had a significant effect (F-count 24.676 > F-table 2.33; sig. 0.000 < 0.05). In conclusion, PKL and organizational experience, both separately and together, play an important role in improving students' career readiness.